2020
DOI: 10.1186/s42358-020-0123-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of Turkish version of Jenkins sleep scale in fibromyalgia syndrome

Abstract: Background: Fibromyalgia syndrome (FMS) has adverse effects on the quality of sleep. The aim of this study was to investigate the validity and reliability of Jenkins Sleep Scale (JSS-TR) in Turkish FMS patients. Methods: FMS patients who met the 2016 fibromyalgia diagnostic criteria were included in the study. Clinical and demographic data of the patients were noted. The relationship between this scale and other functional parameters such as Pittsburgh Sleep Quality Index (PSQI), European Quality of Life Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The results are in line with several previous studies that have found the JSS to be a unidimensional scale with excellent internal consistency 3 6 8. The Cronbach’s alpha of 0.8 seen in the present study was close to the estimates reported by previous research in both general population and populations of people with different health conditions 2 3 5–11 15 16. While the JSS has been studied by employing alpha and EFA by several studies, a confirmatory factor analysis has previously been used by only a single study (Tibubos et al ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results are in line with several previous studies that have found the JSS to be a unidimensional scale with excellent internal consistency 3 6 8. The Cronbach’s alpha of 0.8 seen in the present study was close to the estimates reported by previous research in both general population and populations of people with different health conditions 2 3 5–11 15 16. While the JSS has been studied by employing alpha and EFA by several studies, a confirmatory factor analysis has previously been used by only a single study (Tibubos et al ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have found the JSS to be internally consistent among patients with fibromyalgia,5 11 rheumatoid arthritis,10 ankylosing spondylitis7 and psoriatic arthritis9 as indicated by Cronbach’s alphas between 0.7 and 0.9. Several studies have assessed the internal consistency of the JSS in general and/or healthy populations similarly reporting good to excellent Cronbach’s alphas that vary between 0.8 and 0.9 2 3 6 8 15 16.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The JSS has been adapted to many languages and tested psychometric properties in clinical populations such as rheumatoid arthritis, psoriatic arthritis, ankylosing spondylitis, fibromyalgia, and epilepsy. 20 Ulutatar and Unubol 21 adapted JSS to the Turkish language in fibromyalgia patients and showed adequate psychometric properties (Cronbach α = 0.741).…”
Section: Instruments Assessing Insomnia Symptoms and General Sleep Pr...mentioning
confidence: 99%
“…Total scores vary between 0 and 20, and higher scores demonstrate a higher number of sleep problems. Sleep disorders are considered when the average score is greater than or equal to 2, corresponding to a minimum of one problem night per week (36).…”
Section: The Jenkins Sleep Scale (Jss)mentioning
confidence: 99%